2016
DOI: 10.1103/physrevc.93.064319
|View full text |Cite
|
Sign up to set email alerts
|

Three-body model for an isoscalar spin-triplet neutron-proton pair inSb102

Abstract: We discuss the effect of neutron-proton pair in T = 0, S = 1 channel in the low-lying states of 102 Sb = 100 Sn + p + n nucleus in a three-body model. To this end, we construct a core + p + n three-body model with a model space based on Skrme and relativistic mean field calculations. The latter model is found to be more realistic for the present case due to the pseudo-spin symmetry. It turns out that the (L, S, T ) = (0, 1, 0) coupling scheme of valence nucleons is strongly hindered in 102 Sb with the relativi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thus, the assumption of the inert core might be too simple. In fact, some physical quantities were not reproduced well in the previous work [14,15]. One is able to consider the effect of core breaking by extending the active model space to include one or more lower shells and performing a large scale shell model calculation.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Thus, the assumption of the inert core might be too simple. In fact, some physical quantities were not reproduced well in the previous work [14,15]. One is able to consider the effect of core breaking by extending the active model space to include one or more lower shells and performing a large scale shell model calculation.…”
Section: Introductionmentioning
confidence: 89%
“…The three-body model also has an advantage to focus on the two-body subsystem consisting of two valence particles and provides us a beneficial understanding of pairing correlations in the ground state and spin-isospin excitations. For this reason, in the previous work [14,15], N = Z odd-odd nuclei, which are made up of one proton, one neutron, and an even-even core nucleus with mass A = 14 to 100, were investigated in order to study the effect of isospin T = 0 and T = 1 pairing correlations between the proton and neutron. It was found that the SU(4) multiplets [16], which are characterized by the nucleon spin-isospin plane, are remarkably present in 18 F and 42 Sc and result in strong magnetic dipole (M1) and Gamow-Teller (GT) transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the S = 1 pair interaction on the GT transition strengths have been thoroughly studied * E-mail: kyoshida@ruby.scphys.kyoto-u.ac.jp in N = Z odd-odd nuclei with a three-body model of two nucleons around a spherical core [21][22][23]. A remarkable feature found in N = Z odd-odd nuclei with an LS-closed core ( 4 He, 16 O, 40 Ca) is the appearance of the low-energy state with a strong GT strength.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the S = 1 pair interaction on the GT transition strengths have been thoroughly studied in N = Z odd-odd nuclei with a three-body model of two nucleons around a spherical core [28][29][30]. A remarkable feature found in N = Z odd-odd nuclei with an LS-closed core ( 4 He, 16 O, 40 Ca) is the appearance of the low-energy state with a strong GT strength.…”
Section: Introductionmentioning
confidence: 99%